Social Studies, Science, and Civics: Teacher Education and Citizen Science in the 21st Century - Tippett, Christine; McLean, Lorna R.; Bergen, Jennifer; Baroud, Jamilee (Alberta Journal of Educational Research, 2021)
Citizen science, research in which members of the public actively contribute scientific data, has recently evolved as a means to support scientific inquiry in the classroom, particularly in fields related to ecology and environmental science. Our research focuses on a collaborative project with teacher candidates, a science education professor, and a social studies education professor at a Canadian university. Teacher candidates were engaged in the classroom and beyond as they explored topics related to civics education and evidence-based decision making. Our findings demonstrate the potential effectiveness of a citizen science lens for science, social studies, and generalist teachers. Key Words: citizen science, citizenship/civics education, science education, social studies education, teacher education La science citoyenne, c'est-à-dire la recherche dans laquelle les membres du public contribuent activement aux données scientifiques, a récemment évolué comme un moyen de soutenir la recherche scientifique en classe, en particulier dans les domaines liés à l'écologie et aux sciences de l'environnement. Notre recherche porte sur un projet de collaboration avec de futurs enseignants, un professeur d'enseignement des sciences et un professeur d'enseignement des sciences sociales dans une université canadienne. Les candidats à l'enseignement se sont engagés dans la salle de classe et au-delà en explorant des sujets liés à l'éducation civique et à la prise de décision fondée sur des preuves. Nos résultats démontrent l'efficacité potentielle d'une optique de science citoyenne pour les professeurs de sciences, d'études sociales et les enseignants généralistes. Mots clés : science citoyenne; éducation à la citoyenneté/civique; enseignement des sciences; enseignement des études sociales; formation des enseignants